Cognitive engagement during reading on digital tablet: Evidence from concurrent recordings of postural and eye movements. Issue 11 (November 2020) - Ballenghein, Ugo; Kaakinen, Johanna K; Tissier, Geoffrey; Baccino, Thierry
The present study utilised a novel combination of eye movement and motion capture recordings to examine cognitive engagement during reading on a hand-held tablet computer. Participants read a multiple-page text with a specific task in mind and after reading recalled the main contents of text from memory. The results showed that head distance from screen was slightly shorter, and readers spent longer time reading task-relevant than irrelevant segments of text and had better memory for task-relevant than irrelevant text information, indicating that there are task-induced momentary changes in engagement during reading. Moreover, head motion and individual fixation durations decreased during the course of reading of relevant segments, and even though there was an overall increase in table motion during reading, the slope of this increase was steeper for irrelevant than relevant text segments. These results suggest that readers become more engaged with relevant and less engaged with irrelevant text segments across the text. The novel methodological combination of eye and postural movements seems to provide valuable information about cognitive engagement during reading in digital environments. The cumulation of evidence from this and previous studies suggests that reading on a tablet affords different interactions between the reader and the text than reading on a computer screen. Reading on a tablet might be more similar to reading on paper, and this may impact the attentional processes during reading.